2022
DOI: 10.3390/life12010079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre-Term Birth on the Cardio-Respiratory Responses to Hypoxic Exercise in Children

Abstract: Pre-term birth is associated with numerous cardio-respiratory sequelae in children. Whether these impairments impact the responses to exercise in normoxia or hypoxia remains to be established. Fourteen prematurely-born (PREM) (Mean ± SD; gestational age 29 ± 2 weeks; age 9.5 ± 0.3 years), and 15 full-term children (CONT) (gestational age 39 ± 1 weeks; age 9.7 ± 0.9 years), underwent incremental exercise tests to exhaustion in normoxia (FiO2 = 20.9%) and normobaric hypoxia (FiO2 = 13.2%) on a cycle ergometer. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…This highlights that cardiovascular rather than diffusive mechanisms at muscle level underlie the reduced exercise capacity reported in the present study as well as by a growing number of other investigations (7-10). Moreover, despite preliminary evidence on animal models (16) and preterm kids (47), the present work is the first to demonstrate a lower sensitivity to the detrimental effects of hypoxia in preterm adults on exercise cardiac hemodynamics compared with their term born peers.…”
Section: Discussioncontrasting
confidence: 58%
“…This highlights that cardiovascular rather than diffusive mechanisms at muscle level underlie the reduced exercise capacity reported in the present study as well as by a growing number of other investigations (7-10). Moreover, despite preliminary evidence on animal models (16) and preterm kids (47), the present work is the first to demonstrate a lower sensitivity to the detrimental effects of hypoxia in preterm adults on exercise cardiac hemodynamics compared with their term born peers.…”
Section: Discussioncontrasting
confidence: 58%
“…Even though human investigations and animal models on the mechanisms by which premature birth per se leads to increased blood pressure (BP) remain limited, recent work demonstrated impaired vascular structure and function in young adults born preterm with high systolic blood pressure (SBP) in adult life (Lazdam et al., 2010 ). Moreover, increasing evidence demonstrates specific cardiovascular (Barton et al., 2021 ; Goss et al., 2015 ; Narang et al., 2022 ), respiratory (Bates et al., 2014 ; Debevec et al., 2019 , 2022b ; Duke et al., 2014 ; Farrell et al., 2015 ; Narang et al., 2022 ) and molecular (Martin et al., 2018 and 2020 ) responses to both hypoxia and hypercapnia in prematurely born children and young adults. While some authors reported beneficial effects of preterm birth during acute hypoxia exposure (Farrell et al., 2015 ; Goss et al., 2015 ), others suggested exaggerated and/or impaired responses to a reduced oxygen (O 2 ) availability (Barton et al., 2021 ; Bates et al., 2014 ; Debevec et al., 2019 ) or increased CO 2 breathing (Manferdelli et al., 2021 ; Rigatto et al., 1975 ).…”
Section: Introductionmentioning
confidence: 99%